TEORI DAN MODEL PENGEMBANGAN KURIKULUM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Sinta Titis Pangesti Putri Ciptami; Prisca Anggun Ferian Putri; Imam Junaris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the theories and models of curriculum development in Islamic Religious Education (PAI). The curriculum plays a crucial role as a guideline in the learning process, not only focusing on cognitive aspects but also on character building and students’ spiritual values. This research employs a library research method by reviewing various sources such as books, journals, and relevant documents. The findings indicate that curriculum development theories proposed by scholars such as Comenius, Tyler, Taba, and Vicencio provide a conceptual foundation for designing, implementing, and evaluating curricula. Furthermore, curriculum development models such as Tyler, Taba, Saylor, Alexander and Lewis, and Oliva offer systematic steps that can be applied in developing PAI curricula. By integrating these theories and models, the PAI curriculum can be developed more effectively, contextually, and in line with current developments, thereby fostering students who are faithful, pious, and possess noble character.